Manajemen Organisasi Klub Senam Lantai Tunas Muda Gymnastic Brebes Tahun 2023 - Hanif, Akromi; Agus Darmawan (Universitas Negeri Semarang, 2024)
The management study of the Tunas Muda Gymnastic Floor Club in Brebes 2023 focuses on achievements and challenges related to facility constraints and coaching management. The research aims to enhance insights into the management and development programs for floor gymnastics. A qualitative descriptive study was conducted on the Tunas Muda Gymnastic Floor Club in Brebes in 2023, exploring management and performance development programs. This investigation utilized interviews, observations, and documentation. Data analysis employed qualitative descriptive methods using triangulation techniques to assess the improvement in the quality of performance development and club management for similar sports. The Tunas Muda Gymnastic Floor Club in Brebesattained significant accomplishments through effective management. Challenges encountered included limited facilities, time constraints, minimal promotion, and inadequate funding. In the SWOT analysis, the club exhibited strong management and satisfactory athletes but lacked facilities. Management and performance development at the Tunas Muda Gymnastic Floor Club in Brebes are crucial for athletes' achievements. Despite achieving commendable results, the club needs to address these challenges. With appropriate strategies, the club can progress, achieve higher accomplishments, and contribute to the development of floor gymnastics in Brebes.